Deskripsi Penggunaan Lahan Kawasan Pesisir - Muhabiba; La Harudu; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2023)
Pajala Village is a village that has a coastal area with abundant resources. The resources found in coastal areas can be one of the basic capital for development in Pajala Village. This study aims to: 1) describe land use in the coastal area of Pajala Village; and 2) analyzing the types of land use that dominate the coastal area of Pajala Village. The method used in this research is qualitative research with direct field observation. The results showed that: 1) land use in the coastal area of Pajala Village, Maginti District is a protected area, residential area, cultivation area, fishery area, industrial area, tourist area, and port and wharf area with beach type B; and 2) this area is dominated by residential and government buildings, namely, 12.01 km2 which is on a slope of 0–8%.